Determination of Hydrotreated Vegetable Oil (HVO) in Blended Diesel Fuel Using Calibration of Isooctane by GC-FID Measurement - Novilia Novilia; Sylvia Ayu Bethari; Handajaya Rusli; Muhammad Bachri Amran (Testing Center for Oil and Gas LEMIGAS, 2025)
Hydrotreated vegetable oil (HVO) is emerging as a promising renewable fuel that is sharing similar chemical characteristics with fossil diesel, making it suitable as a blending component. However, this similarity is presenting challenges in distinguishing and quantifying HVO in diesel blends. The present study is focusing on developing a simple, cost-effective, and reliable method using gas chromatography with flame ionization detection (GC-FID) for determining HVO content in diesel mixtures. Two candidate markers, hexadecane (C₁₆H₃₄) and heptadecane (C₁₇H₃₆), are being evaluated based on linearity, detection limits, and accuracy. Calibration curves are being constructed using HVO–isooctane mixtures from 0 to 50% v/v HVO. The heptadecane peak is demonstrating superior performance with excellent linearity (R² = 0.9994), a low detection limit (1.77% v/v), and quantification limit (5.36% v/v). In contrast, the hexadecane peak is showing similar linearity but lower sensitivity. Accuracy tests are being conducted on diesel samples spiked with 10% HVO, showing recovery rates above 95% for both markers. Overall, heptadecane is proving to be a consistent and reliable marker for quantifying HVO in diesel blends using GC-FID.